Effects of body mass-based resistance training on measures of physical fitness and musculotendinous injury incidence and burden in U16 male soccer players - Martín, L. T.; Raya-González, J.; Ramirez-Campillo, R.; Chaabene, H.; Sánchez-Sánchez, J. (Research in Sports Medicine, 2023)
This study examined the effects of body mass-based resistance training (bmRT) on selected measures of physical fitness and injury incidence and burden in soccer players. Forty-six U16 male soccer players were randomly assigned to an control (CG; n = 26) or experimental group (EG; n = 20) Countermovement jump (CMJ), change of direction (CoD) (i.e., 20 m with one CoD), and linear sprint over 30 m were assessed before and after a 15-weeks training. Any type of musculotendinous injury that occurred throughout the intervention period was recorded. Between-group difference was noted at post-test for CMJ (p = 0.008). Pre-to-post training values increased in the EG (effect size [ES] = 1.01) while in the CG no pre-to-post changes were detected (ES = 0.27). No between-group differences at post-test were observed for sprint and CoD tests. Differences in injury burden were reported (33.28 [CG] vs. 9.55 [EG] absence days/1,000 hours exposure, rate ratio = 3.49, 95% CI 2.03-6.00, p < 0.001), but not in injury incidence. A bmRT programis suitable for improving jumping height but not linear and CoD speed performance. Additionally, bmRT may reduce injury burden, and therefore, the severity of musculotendinous injuries in U16 male soccer players.